Vivid birds do not initiate flight sooner despite their potential conspicuousness. Issue 4 (1st August 2015) - Hensley, Nicholai M.; Drury, Jonathan P.; Garland, Theodore; Blumstein, Daniel T.
Abstract: The distance from an approaching threat at which animals initiate flight -- flight-initiation distance (FID) -- is a sensitive metric of variation in risk, but the effects on FID associated with the risk of possessing highly detectable external coloration are unknown. We tested whether variation in the degree of plumage vividness in birds explained variation in flight-initiation distance. After controlling for body mass, the distance at which the experimental approach began, and phylogenetic relatedness, plumage vividness was not a predictor of FID. Contrary to the expectation that vividness affects risk, and therefore risk assessment, these results suggest that birds do not compensate for greater visual conspicuousness by fleeing sooner from approaching threats.